Fatal fulminant hepatitis in a patient taking abiraterone acetate: a case report - Akpokavie, Dela; Gubert, Capucine; Abdelli, Imene; Stern, Alix O'Meara; Zender, Hervé (Frontiers in Medicine, 2023)
Abiraterone acetate is a steroidal inhibitor of cytochrome P450 17A1 indicated in the treatment of metastatic prostate cancer. This report examines the case of a 66-year-old patient diagnosed with prostate adenocarcinoma that had metastasized to the bones and lymph nodes. Treatment with abiraterone acetate and corticosteroid co-administration as well as LH-RH analog hormone therapy was initiated. Four and a half months later, the patient consulted for deterioration of general condition. Biologically, he developed a fulminant hepatitis of which he eventually died. An infectious or metabolic origin was ruled out. Oncological cause by either disease progression or second neoplastic process was eliminated by means of imaging. Hepatic toxicity was imputed to the treatment with abiraterone acetate. This case suggests that fulminant hepatitis on abiraterone acetate may be underestimated, and underscores the importance of regular monitoring of liver tests on this therapy.